Impaired neurobehavioral alertness quantified by the psychomotor vigilance task is associated with depression in the Wisconsin Sleep Cohort study - Plante, David T.; Hagen, Erika W.; Ravelo, Laurel A.; Peppard, Paul E. (Sleep medicine, 2020)
Excessive daytime sleepiness plays an important role in the presentation and course of mood disorders. Standard objective measures of daytime sleep propensity are of little to no value in depressive illness. This study examined the psychomotor vigilance task (PVT), an objective measure of neurobehavioral alertness, and its cross-sectional and longitudinal associations with depressive symptomatology in the Wisconsin Sleep Cohort Study. The sample consisted of 1569 separate 10-min PVT assessments conducted in 942 unique individuals. Cross-sectional and longitudinal conditional logistic regression models were used to estimate associations between the primary outcome of depression symptomatology (adjusted Zung scale≥50) and six separate PVT variables: mean reciprocal reaction time (1/RT); total lapses (RTs≥500 msec; LAPSE); total false responses (FALSE); reciprocal of the mean of the 10% fastest (FAST) and 10% slowest (SLOW) RTs; and slope of the linear regression line for all transformed 1/RTs (SLOPE). In fully-adjusted cross-sectional models, 1/RT, LAPSE, FAST, and SLOW were each significantly associated with depression, such that worse neurobehavioral alertness was associated with higher odds of depressive symptomatology. Similar, though attenuated, findings were observed in fully-adjusted conditional longitudinal models that examined within-subject changes in depression status in the subset of participants with repeated PVT assessments. FALSE and SLOPE were not associated with depression in either cross-sectional or conditional longitudinal models. These findings suggest components of the PVT are associated with depressive symptomatology. Further research is indicated to clarify the role of the PVT in the assessment of hypersomnolence in mood disorders. •Excessive daytime sleepiness plays a key role in the course of depression.•No objective hypersomnolence measure is established as useful in mood disorders.•The psychomotor vigilance task (PVT) is a measure of neurobehavioral alertness.•Findings demonstrate PVT components are significantly associated with depression.•The PVT may be a salient objective measure of hypersomnolence in depression.